Safety of Intravenous Iron – Cosmofer and Monofer Therapy in Peritoneal Dialysis and Non-Dialysis-Dependent Chronic Kidney Disease Patients. Issue 2 (March 2019) - Sivakumar, Chaamanti; Jubb, Vikki M.; Lamplugh, Archie; Bhandari, Sunil
Safety of parenteral iron therapy is critical and has been demonstrated in several studies, but concerns persist on safety. We performed a retrospective single-center study investigating the safety and efficacy of parenteral iron administration using 2 iron preparations—Monofer and Cosmofer (Pharmacosmos A/S, Holbaek, Denmark)—in patients with chronic kidney disease (CKD), on peritoneal dialysis (PD) and non-dialysis. A database of CKD patients receiving intravenous (IV) iron was analyzed. Side effects were recorded during infusion, post-infusion, and after 48 hours. In a population of CKD patients (non-dialysis and PD), IV iron is safe with few major adverse effects for these 2 IV iron preparations studied with similar dosing schedules. These data provide reassurance on the relative short-term safety of IV iron preparations regarding acute infusion-related hypersensitivity reactions.